A CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND INDONESIAN PREFIXES AND SUFFIXES IN THE DESCRIPTIVE TEXTS OF STUDENT’S TEXTBOOKS - Mena, Vera Veti; Saputri, Kurnia (English Community Journal, 2018)
This study is aimed at describing the kinds of the English and Indonesian prefixes and suffixes mostly found in the descriptive text of student’s and finding the similarities and dissimilarities. The writer used descriptive qualitative research method. To collect the data, the writer used documentation technique. In analyzing the data the writer used descriptive analysis. After investigating the data, the writer found out four types of English prefix; quantified, locative, temporal, and negation prefixes. English suffixes have four types; nominal, verbal, adjectival, and adverbial suffixes, and five types of Indonesian prefixes; forming verb, forming adjectival, forming noun, forming numeral, and there forming interrogative. The writer also found out thirty two prefixes and suffixes words categorized as English Prefixes and Suffixes, and twenty prefixes and suffixes words categorized as English Prefixes and Suffixes. The writer found out the similarities and dissimilarities. The similarities between English Indonesian prefixes and suffixes in the descriptive text were on prefixes in line with quantity, and suffixes in line with nominal, verbal, and adjectival suffixes. While the dissimilarities were on prefixes and suffixes. In English prefixes, there were no types of prefixes that forming verb, adjective, noun, and interrogative. While in Indonesian prefixes, there were no types of prefixes such as locative, temporal, and negation prefixes. In English suffixes there were no forming numeral and interrogative. In Indonesian There was no adverbial suffix.